FAMILY SUPPORT, DURATION OF INCARCERATION AND INMATES’ INTENT TO RETURN TO CRIME IN AGODI PRISON, IBADAN, NIGERIA - Ajibola Abdulrahamon Ishola (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
Criminal intent is a major precursor of reoffending behaviour and one of the big issues for ex- convicts and investigations have been undertaken to determine reasons of re-offending within imprisoned population. Evidence is still needed on the influence of family support and incarceration duration on intent to reoffending among inmates in Nigeria. Prison inmates (291) were selected for a cross-sectional survey in the Agodi prison. Results revealed a significant inverse relationship among family and partner support and criminal intent behavior.  Family and partner support predicted criminal intent. Short duration of stay (less than 2 years) in the prison among inmates awaiting trial was associated with higher criminal intent. It was concluded that low family/partner support and shorter stay in prison were possible precursor of reoffending among inmates in Agodi prisons. Persistent assessment of institutional environment risk for re-offending among inmates using valid risk assessments tools was recommended.